Transfusion prevention using erythropoietin, parenteral sucrose iron, and fewer phlebotomies in infants born at ≤30 weeks gestation at a high altitude center: a 10-year experience (2021)
Introduction: Red blood cell transfusions in infants born at ≤30 weeks gestation are frequent. Erythropoietin therapy reduces transfusions. An increase in hematocrit is an adaptive response at high altitudes but a guaranteed source of iron is necessary for adequate erythropoiesis. Methods: A retrospective cohort study was done to compare red blood cell transfusion practices of the 2019 EpicLatino (EPIC) Latin America network database with a single unit at 2650 m above sea level (LOCAL). The data from LOCAL for three time periods were compared over 10 years based on changes in erythropoietin dose and fewer phlebotomies. The number of cases that received transfusions and the total number of transfusions required were compared. Adjustments were made for known risk factors using a multivariate regression analysis. Results: Two hundred and twenty-one cases in LOCAL and 382 cases from EPIC were included. Overall basic demographic characteristics were similar. In EPIC a significantly higher rate of infection (28% vs. 15%) and outborn (10% vs. 1%) was found, but less necrotizing enterocolitis (9% vs. 15%) and use of prenatal steroids (62% vs. 93%) than LOCAL (p < 0.05). EPIC patients received more transfusions (2.6 ± 3 vs. 0.6 ± 1 times) than LOCAL (p < 0.001) and received them significantly more frequently (61% vs. 25%). Within the LOCAL time periods, no statistically significant differences were found other than the need for transfusions (1st 32%, 2nd 28%, 3rd 9%, p = 0.005) and the average number of transfusions (1st 0.8 ± 1.6, 2nd 0.7 ± 1.3, 3rd 0.1 ± 0.3, p = 0.004). These differences remained significant after multivariate regression analysis and adjusting for risk variables. Conclusion: The combination of erythropoietin, parenteral sucrose iron, fewer phlebotomies during the first 72 h, and delayed umbilical cord clamping seem to reduce red blood cell transfusion needs. This can be extremely important in high altitude units where higher hematocrit is desirable but may also be valuable at sea level.